2013
DOI: 10.1038/cddis.2013.320
|View full text |Cite
|
Sign up to set email alerts
|

Smac mimetic and demethylating agents synergistically trigger cell death in acute myeloid leukemia cells and overcome apoptosis resistance by inducing necroptosis

Abstract: Evasion of apoptosis, for example, by inhibitor of apoptosis (IAP) proteins, contributes to treatment resistance and poor outcome in acute myeloid leukemia (AML). Here we identify a novel synergistic interaction between the small-molecule second mitochondria-derived activator of caspases (Smac) mimetic BV6, which antagonizes X-linked IAP, cellular IAP (cIAP)1 and cIAP2, and the demethylating agents 5-azacytidine or 5-aza-2′-deoxycytidine (DAC) to induce cell death in AML cells, including apoptosis-resistant ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 45 publications
8
78
0
Order By: Relevance
“…29,43 Recently, combination treatment with a demethylating agent largely improved the tumor-suppressive effects of Smac mimetics in several cancer models. 27,44 In addition to these, numerous new compounds including LCL161 and birinapant are currently in phase I and II clinical trials. 5,14 As our data suggest, cIAP2 sensitivity against Smac mimetics in relation to USP11 expression should be considered in the abovementioned combination therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,43 Recently, combination treatment with a demethylating agent largely improved the tumor-suppressive effects of Smac mimetics in several cancer models. 27,44 In addition to these, numerous new compounds including LCL161 and birinapant are currently in phase I and II clinical trials. 5,14 As our data suggest, cIAP2 sensitivity against Smac mimetics in relation to USP11 expression should be considered in the abovementioned combination therapies.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 While several studies have supported hypotheses for how cIAP2 survives in the presence of Smac mimetics, numerous independent studies have also shown that cIAP2 can be efficiently degraded by Smac mimetics in various cell lines. [27][28][29][30][31][32] These observations suggest the existence of other factors that specifically regulate cIAP2 stability upon Smac mimetic treatment. In this study, we propose a new mechanism involving USP11-mediated cIAP2 regulation.…”
mentioning
confidence: 85%
“…We previously reported that Smac mimetics can act as chemosensitizers in combination with anticancer drugs, 30,46 demethylating agents or glucocorticoids 45,47 and as radiosensitizer. 31,48,49 Our findings showing that BV6 cooperates together with Obatoclax to induce cell death in CLL cells, but not together with ABT-263 may be related to the differential activity profiles of these BH3 mimetics, as Obatoclax antagonizes BCL-2, BCL-xL, BCL-W and MCL-1, whereas ABT-263 targets BCL-2, BCL-xL and BCL-W, but not MCL-1.…”
Section: Discussionmentioning
confidence: 99%
“…These results provide the basis for a randomized phase II study comparing birinapant in combination with 5-Aza against 5-Aza alone in the first-line setting for patients with MDS (70). Consistently, recent evidence from preclinical studies revealed synergistic antileukemic effects of Smac mimetics plus 5-Aza against AML cells, including AML stem/progenitors (55,56).…”
Section: Smac Mimetic-based Combination Therapies: Clinical Translationmentioning
confidence: 54%
“…Smac mimetics were also shown to enhance the sensitivity toward radiotherapy both in vitro and in preclinical in vivo models of human cancers (42)(43)(44)(45)(46). Furthermore, synergistic induction of cell death was reported for Smac mimetics in combination with novel agents, including TRAIL receptor agonists (47)(48)(49)(50)(51)(52)(53)(54), epigenetic drugs (55)(56)(57), or immunotherapies (58-61). Together, these preclinical studies underscore the potential of Smac mimetics to sensitize cancer cells for cytotoxic therapies by lowering the threshold to trigger cell death.…”
Section: Clinical Efficacy Of Smac Mimetics As Monotherapymentioning
confidence: 99%